Defending Application Layer DDoS Attacks via Multidimensional Parallelotope. (30th December 2020) - Zhao, Xiaolin; Peng, Hui; Li, Xiang; Li, Yue; Xue, Jingfeng; Liang, Yaoyuan; Pei, Mingzhe
Abstract : The Internet is more and more integrated into people's life; because of the complexity and fragility of the network environment, network attack presents a more and more serious trend. Application Layer DDoS (AL-DDoS) attack is the most complex form of DDoS attack, which is hindering the availability for the legitimate users by taking up a large number of requests of web server. The paper introduced the concept of behavior utility to portray the network. The concept of attack and defense utility was defined by a specific property which was the manifestation of the network risk after the offset of attack and defense. In the utility model, traffic metrics were mapped to the multidimensional parallelotope in the Euclidean space to express as a diagonal matrix. To determine the threshold status, the defense strategies of load balancing and limiting the maximum number of connections were used with different attack scales. Finally, the attack and defense utility value was calculated to evaluate the network risk level. The proposed method can master the capacity of network system against each attack means and the defense capability of network system. Its availability and accuracy are verified by comparing with the relevant works.